Les relations économiques Est-Ouest 1975-1985 : Bilan et perspectives - Lavigne, Marie (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1981)
The "golden age" in East-West trade is over since 1975. However, the period following the beginning of the world crisis, up to 1980, was not so gloomy as it was expected in the mid seventies. Although at a reduced rate, compared with the previous period, there was a significant increase in trade and especially exports of Eastern Europe to the West. Apart from the Polish case, indebtedness of Eastern Europe did not soar in dramatic proportions, and some countries achieved a stabilization of their trade balance with the West at the end of the decade; East-West industrial cooperation developed; the adverse political climate, which deteriorated sharply in 1980, did not stop trade flows and did not entail a reorientation toward Comecon of East European trade ; notwithstanding the standstill of Comecon EEC negociations, several important arrangements were signed between the Common Market and individual Comecon member countries.The prospects up to 1985 are not very bright, especially when considering the recession in Western economies, the structural difficulties impeding the reform movement in the East European economies, the Polish crisis, the financial difficulties of some other countries. The future of East-West trade is linked to the energy constraints of the Eastern bloc, its agricultural situation ; it may benefit from the developments in the socialist integration process.